The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1200/jco.2005.19.554
|View full text |Cite
|
Sign up to set email alerts
|

Deletions Affecting Codons 557-558 of the c-KIT Gene Indicate a Poor Prognosis in Patients With Completely Resected Gastrointestinal Stromal Tumors: A Study by the Spanish Group for Sarcoma Research (GEIS)

Abstract: Deletions affecting codons 557 to 558 are relevant for the prognosis of RFS in GIST patients. This critical genetic alteration should be considered to be a new prognostic stratification variable for randomized trials exploring imatinib mesylate in the adjuvant setting in GIST patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
235
2
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(268 citation statements)
references
References 26 publications
21
235
2
10
Order By: Relevance
“…Initially it is proposed that the presence of genetic mutations could be used as a marker to predict malignancy or poor prognosis. [38][39][40][41][42][43] Since approximately 90% of the GISTs contain either KIT or PDGFRA gene mutations, it is apparently not a reliable criterion. 44 Studies indicated that the type of mutation may predict prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially it is proposed that the presence of genetic mutations could be used as a marker to predict malignancy or poor prognosis. [38][39][40][41][42][43] Since approximately 90% of the GISTs contain either KIT or PDGFRA gene mutations, it is apparently not a reliable criterion. 44 Studies indicated that the type of mutation may predict prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…44 Studies indicated that the type of mutation may predict prognosis. 40,41,[45][46][47] On the basis of our unpublished data and recent reports, the most reliable mutation type with independent prognostic role was homogenous deletion in exon 11 of KIT gene. 48 However, the frequency of this homogenous mutation is rare.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] In particular, deletions involving codons 557 and/or 558 are associated with malignant behavior. [19][20][21] Aside from exon 11 mutations, between 7 and 10% of GISTs have a mutation in an extracellular domain encoded by exon 9. 22 These mutations are thought to mimic the conformational change that the extracellular KIT receptor undergoes when ligand is bound.…”
Section: Kitmentioning
confidence: 99%
“…6 Although GISTs exhibit a spectrum of biologic behavior from benign to malignant, the molecular mechanism of tumor progression has not been fully clarified. Previous studies have reported the prognostic significance of tumor size, mitotic counts, tumor grade, Ki-67 labeling index (LI), 7 KIT mutation type, 4,8,9 p16 inactivation 10 and overexpression of cell-cycle regulators such as cyclin A, cyclin B1 and cdc2. 11 Angiogenesis is one of the key steps in the growth and metastasis of solid tumors.…”
mentioning
confidence: 99%